(untitled) (UNWE Yearbook, 2005)
The expected results after applying the CAP’s measures in Bulgaria are contradictory. Concerning the crop production the effects of CAP’s measures are estimated to be positive. The areas under cereals and sunflower will increase and as a result their production will grow. Since the expected change in the consumption of these products is insignificant, the exported production is likely to increase.The CAP impact on the sheep-breading will be also positive. After the support for the producers in the sector, the number of animals will increase, as well as the production of lamb and mutton. As it concerns the cattle-breeding the results are contradictory. The restriction of milk quota will lead to considerable decrease of milk, veal and beef production.The lower effects from CAP for the agriculture and the highly negative results for the cattle-breeding are due to many factors. The low level of the agricultural production in Bulgaria in the pre-accession period influenced the negotiations with EU for support in the sector. The expected low CAP’s effect from the majority of the small semi commodity producers in the country, as well as numerous institutional problems are also among the determinative factors that leaded to, some extent, disappointing results.